Pengaruh Kebijakan Pemerintah dan Dukungan Lembaga Keuangan terhadap Perkembangan UMKM di Kabupaten Tasikmalaya - Adi Rafli Setiadi; Alfin Nur Arifah; Herdiyanti Herdiyanti; Ardhiansyah Ardhiansyah (CV. Kalimasada Group, 2026)
This study aims to analyze the influence of government policy and financial institution support on the development of Micro, Small, and Medium Enterprises (MSMEs) in Tasikmalaya Regency. Although MSMEs play a vital role in regional economic growth, they continue to face numerous challenges, including limited access to financing, low financial literacy, marketing difficulties, and technological adaptation. This quantitative study used a survey approach with 100 MSME actors selected through purposive sampling. Data were collected via questionnaires and analyzed using validity tests, reliability tests, classical assumption tests, and multiple linear regression with IBM SPSS Statistics. The results show that government policy has a positive and significant effect on MSME development (β = 0.355, p < 0.001). Financial institution support also has a positive and significant effect (β = 0.458, p < 0.001). The coefficient of determination (R² = 0.667) indicates that 66.7% of the variation in MSME development can be explained by these two variables. This study highlights the importance of stronger synergy between government policies and financial institutions to accelerate MSME growth in Tasikmalaya Regency.